Erythrocyte fatty acid status in a convenience sample of residents of the Guatemalan Pacific coastal plain. (July 2015) - Solomons, Noel W.; Bailey, Eileen; Soto Méndéz, María José; Campos, Raquel; Kraemer, Klaus; Salem, Norman
Abstract: We report the fatty acid composition, and in particular, the n-3 and n-6 long-chain polyunsaturated fatty acids (LCPUFA), in erythrocytes from a convenience sample of 158 women and 135 schoolchildren residing in the southern Pacific Coast of Guatemala. Erythrocyte fatty acids were analyzed by gas-liquid chromatography with flame ionization detection and the profiles were expressed as a weight percent; the Omega-3 Index values were also determined. Schoolchildren had significantly higher mean ARA and total n-6 fatty acid levels than the women. Women had significantly higher EPA fatty acid levels than schoolchildren, but the reverse was true for DHA. For mean total n-3 fatty acid concentration, women and schoolchildren had similar values. The red cell weight percentages of selected fatty acids were also similar in women and schoolchildren. As compared with erythrocyte fatty acid data from developed countries, Guatemalan women and schoolchildren had consistently lower LCPUFA values. The traditional diet of Guatemalans living in the Pacific coastal region provided a worse erythrocyte fatty acid profile than that typically obtained from a Western diet. Additional fatty acid composition studies with associated dietary intake data in other inland locations may be useful for the interpretation of the nutritional status of Guatemalan children and adults.